STRATEGY OF SALES VOLUME EXPANSION FOR MSME GROUP IN BANTARJAYA VILLAGE, RANCABUNGUR - BOGOR - Daru Asih; Yuli Harwani; Yanto Ramli; Yusliza Mohd Yussoff; Eko Tama Putra Saratian; Mochamad Soelton (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2023)
The main problem of a small industry is not only to achieve a stable high level of performance but also to maintain a position in the market while competing with all the unexpected challenges that will come. the situation in Bantarjaya Village, several problems can be formulated as obstacles. These problems include how to create innovations related to product distribution patterns that experience difficulties in production and increase sales volume. Efforts to create innovations related to product distribution patterns that experience difficulties in production and increase sales volume. this needs to be done by providing knowledge and skills in applying pilot-based marketing management methods to increase revenue. And support coaching motivation and managerial and entrepreneurial skills. Currently, MSMEs spread across Bantarjaya Village are a reference in producing processed snacks. Like, dodol, rangginang, and other pastries, in the home food product industry. Trading services are of course very important so that society continues to develop in a better direction. However, until now his team together with all the human resources of the Bantarjaya village government have continued to struggle to achieve unfinished work programs. Business continuity is a non-static phenomenon due to several reasons such as global climate conditions, scarce resources, insecure and competitive global scenarios, imminent population increase, political instability, economic crises, and innovative new technologies in the world.